Acupressure Massage Training in Improving Toddler Appetite as Strengthening Prevention of Malnutrition and Stunting: Pelatihan Pijat Akupresur dalam Meningkatkan Nafsu Makan Balita sebagai Penguatan Pencegahan Kurang Gizi dan Stunting - Arya, Bima; Nihayah, Faridah; Cholifah, Siti (Procedia of Social Sciences and Humanities, 2022)
Malnutrition and stunting are health problems in children and toddlers that are being intensively carried out by the current government. Toddler age is the age most vulnerable to malnutrition. Lack of appetite in children is one of the factors that can trigger malnutrition and stunting. Acupressure or giving stimulation at a certain point is one of the efforts to increase appetite in children and toddlers, but the science of acupressure is not widely known by ordinary people. Meanwhile, effort is an effort that is quite effective in increasing children's appetite because it can be done independently by parents. In Kedungkendo village, there are under-fives with malnutrition and stunting with a number of 14 toddlers out of a total of 258 toddlers (5.4%). The purpose of the community service program is to increase community knowledge and skills as an effort to increase children's appetite which can be done independently by conducting socialization and acupressure massage training.The method of implementing this community service activity is through the stages of a situation analysis survey, collaboration with the village government, village midwives and posyandu cadres, then planning activities for solutions to problems experienced by partners. The team made media for the implementation of the activity in the form of PPT materials, leaflets and posters for acupressure to increase appetite in toddlers. The results of community service activities are an increase in knowledge and cadres about acupressure massage, as many as 25 cadres before the knowledge activity about acupressure 15 people (60%) were not good enough to have good knowledge and 10 people (40%) had good knowledge to have very good knowledge. The participants were very enthusiastic